Corn productivity for silage depending on plant density in the conditions of the Northern Steppe of Ukraine - Kanibolotskyi, I. O.; Каніболоцький, І. О.; Tkalich, Yuriy; Ткаліч, Юрій Ігорович; Tsyliuryk, Оleksandr; Цилюрик, Олександр Іванович; Shevchenko, Sergey; Шевченко, Сергій Михайлович; Kolesnykova, K. V.; Колесникова, К. В.; Yevtushenko, H. O.; Євтушенко, Г. О.; et al. (Дніпровський державний аграрно-економічний університет, 2024)
At the current stage of agricultural development, the adoption of advanced technologies for corn cultivation is of paramount importance. Climatic conditions significantly influence the technology used for corn farming, making it essential to select agro-technological operations suitable for a specific climate. Corn cultivation technology includes the proper selection of a hybrid based on the production needs. It is also crucial to consider the resistance of hybrids to diseases and pests, which can significantly affect the final outcome. The experimental studies conducted in the conditions of the Northern Steppe of Ukraine were aimed to establish the optimal plant density for silage corn to ensure high yield and elevated quality indicators of this crop. Four corn hybrids have been studied: KWS Gendalf (FAO 250), KWS Burito (FAO 380), KWS BigBit (FAO 290), and DN Anshlah (FAO 420) at six different plant densities – 50, 60, 70, 80, 90, and 100 thousand plants/ha. According to the research results, the corn plant mass tended to decrease with increasing plant density of the silage corn from 50 to 100 thousand plants per hectare across all the maturity groups of the hybrids. Specifically, the plant mass gradually decreased from 281.2 to 190.3 g in the mid-late variety DN Anshlah in the BBCH 19 stage; from 278.6 to 244.0 g in the mid-season variety KWS Burito; from 361.4 to 292.3 g in the early-mid variety KWS Gendalf; and from 431.3 to 298.9 g in the early-mid variety KWS BigBit. The leaf area of mid-late DN Anshlah increased linearly from 2,011 to 3,197 cm² when the plant density rose from 50,000 to 70,000 plants/ha, showing a 58.9% increase. However, increasing the density further to 80,000 plants/ha resulted in a 17.1% decrease in the leaf area per plant. The corn cob mass at the BBCH 75 stage displayed a similar trend in the plant mass, namely a decrease with increasing crop density. Gradual decreases in the corn cob mass were noted, specifically, from 329.9 to 213.4 g in the medium-late DN Anshlah variety; from 272.3 to 198.2 g in the medium-ripening KWS Burito variety; from 293.2 to 241.2 g in the medium-early KWS Gendalf variety; and from 348.9 to 244.3 g in the medium-early KWS BigBit variety. The yield of silage corn was the highest at the BBCH 75 growth stage with a plant density of 50,000-70,000 plants per hectare. At different densities, the yield ranged, specifically, 34.91 to 50.41 tons per hectare in medium-late DN Anshlah; 32.85 to 50.86 tons per hectare in medium-maturity KWS Burito; 35.72 to 53.72 tons per hectare in medium-early KWS Gendalf; and 49.13 to 50.87 tons per hectare in medium-early KWS BigBit. The medium-late hybrid DN Anshlah produced the maximum yield of 50.41 tons per hectare with a plant density of 50,000 plants per hectare, while the medium-maturity variety KWS Burito produced 50.86 tons per hectare at 70,000 plants per hectare. The medium-early hybrids KWS Gendalf (52.03 and 53.72 tons per hectare) and KWS BigBit (50.35 and 50.87 tons per hectare) produced such yields at plant densities of 60,000 and 70,000 plants per hectare, respectively. The highest yield was produced by the KWS BigBit hybrid (50.87 tons per hectare) at a density of 70,000 plants per hectare, while the lowest yield (49.13 tons per hectare) was recorded at a density of 90,000 plants per hectare. Thus, the optimal plant density for achieving the highest green mass yield of corn under irrigation in the Northern Steppe region of Ukraine is 70,000 plants per hectare. These results highlight the importance of optimizing plant density to maximize silage corn yield. The identified patterns can serve as a basis for recommendations regarding agronomic practices aimed at improving the efficiency of corn production under various growing conditions. На сучасному етапі розвитку сільського господарства впровадження передових технологій вирощування кукурудзи має першорядне значення. Кліматичні умови суттєво впливають на технологію вирощування кукурудзи, що зумовлює необхідність вибору агротехнічних операцій, які відповідають конкретному клімату. Технологія вирощування кукурудзи включає правильний підбір гібрида з урахуванням потреб виробництва. Важливо також враховувати стійкість гібридів до хвороб і шкідників, що може істотно вплинути на кінцевий результат. Експериментальні дослідження, проведені в умовах Північного Степу України, були спрямовані на встановлення оптимальної густоти рослин кукурудзи на силос для забезпечення високої врожайності та підвищених якісних показників цієї культури. Досліджено 4 гібриди кукурудзи: KWS Gendalf (FAO 250), KWS Burito (FAO 380), KWS BigBit (FAO 290) і DN Anshlah (FAO 420) за шести різних густот рослин – 50, 60, 70, 80, 90 і 100 тис. рослин/га. За результатами досліджень виявлено тенденцію до зменшення маси рослин кукурудзи зі збільшенням густоти силосної кукурудзи від 50 до 100 тис. рослин на гектар за всіма групами стиглості гібридів. Так, у середньопізнього сорту Д. Н. Аншлах у фазі BBCH 19 маса рослин поступово зменшувалася з 281,2 до 190,3 г; від 278,6 до 244,0 г у середньостиглого сорту KWS Burito; від 361,4 до 292,3 г у ранньо-середнього сорту KWS Gendalf; і від 431,3 до 298,9 г у ранньо-середнього сорту KWS BigBit. Площа листя середньопізніх сортів DN Anshlah лінійно зросла з 2011 до 3197 см², коли густота рослин підвищилася з 50 000 до 70 000 рослин/га, демонструючи збільшення на 58,9%. Однак подальше збільшення густоти до 80 000 рослин/га призвело до зменшення площі листя на рослину на 17,1%. Маса качанів кукурудзи на етапі BBCH 75 показала подібну тенденцію у масі рослин, а саме зменшення зі збільшенням густоти посіву. Відзначено поступове зниження маси качанів кукурудзи, а саме у середньопізнього сорту ДН Аншлах від 329,9 до 213,4 г; від 272,3 до 198,2 г у середньостиглого сорту KWS Burito; від 293,2 до 241,2 г у середньораннього сорту KWS Гендальф; і від 348,9 до 244,3 г у середньораннього сорту KWS BigBit. Урожайність силосної кукурудзи була найвищою на фазі росту ВВЧ 75 при густоті рослин 50-70 тис. рослин на гектар. За різної густоти урожайність коливалася, зокрема, у середньопізніх ДН Аншлах від 34,91 до 50,41 т/га; 32,85-50,86 т/га у середньостиглих KWS Burito; 35,72-53,72 т/га у середньоранніх KWS Gendalf; і 49,13-50,87 т/га у середньоранніх KWS BigBit. Середньопізній гібрид ДН Аншлах дав максимальну врожайність 50,41 ц/га при густоті рослин 50 тис. рослин/га, а середньостиглий сорт КВС Буріто — 50,86 ц/га при 70 тис. рослин/га. Середньоранні гібриди KWS Gendalf (52.03 і 53.72 тонни на гектар) і KWS BigBit (50,35 і 50,87 тонн на гектар) дали такі врожаї при густоті рослин 60 000 і 70 000 рослин на гектар відповідно. Найбільшу врожайність дав гібрид KWS BigBit (50,87 т/га) за густоти 70 тис. рослин/га, а найменшу (49,13 т/га) – за густоти 90 тис. рослин/га. Так, оптимальна густота рослин для досягнення найвищої врожайності зеленої маси кукурудзи на зрошенні в Північному Степу України становить 70 тис. рослин з гектара. Ці результати підкреслюють важливість оптимізації густоти рослин для максимізації врожаю силосної кукурудзи. Виявлені закономірності можуть бути покладені в основу рекомендацій щодо агротехнічних прийомів, спрямованих на підвищення ефективності виробництва кукурудзи в різних умовах вирощування.
Продуктивність кукурудзи на силос залежно від густоти рослин в умовах Північного Степу України
Keywords: silage corn; силосна кукурудза; plant density; густота рослин; plant height; висота рослини; corn ear weight; маса колоса; moisture; вологість; yield; врожайність